2020
DOI: 10.1136/bmjdrc-2020-001568
|View full text |Cite
|
Sign up to set email alerts
|

Impaired glucose regulation, depressive symptoms, and health-related quality of life

Abstract: IntroductionThis study aims to investigate whether the associations between impaired glucose regulation and health-related quality of life are modified by severity or type of depressive symptoms.Research design and methodsFor this cross-sectional study, we included 1939 individuals (mean age 61.5 years) from the Helsinki Birth Cohort Study. Between 2001 and 2004, a standard 2-hour 75 g oral glucose tolerance test was applied to define normoglycemia, pre-diabetes, and newly diagnosed diabetes. Information on pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 38 publications
0
9
0
Order By: Relevance
“…We observed relatively low consumption of these products across the categories of SPH; hence, only the group of poor SPH was significantly associated with sugary product consumption. We would expect for inverse associations to be consistent in future studies, particularly in samples with higher consumption of similar food items, and thereof, marked detrimental effects on lifestyle and well-being [ 46 , 47 ]. Physical activity on the other hand, is known for its positive impact on health in a dose-response relationship [ 48 , 49 ].…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…We observed relatively low consumption of these products across the categories of SPH; hence, only the group of poor SPH was significantly associated with sugary product consumption. We would expect for inverse associations to be consistent in future studies, particularly in samples with higher consumption of similar food items, and thereof, marked detrimental effects on lifestyle and well-being [ 46 , 47 ]. Physical activity on the other hand, is known for its positive impact on health in a dose-response relationship [ 48 , 49 ].…”
Section: Discussionmentioning
confidence: 89%
“…Similar chains of events have been described in clinical trials that include behavioral counseling for dietary interventions [ 40 , 42 ]. In contrast, sugary products were included for their role as determinants of body composition and glucose metabolism, as well as their negative effects on health and well-being [ 43 , 44 , 45 , 46 ]. We observed relatively low consumption of these products across the categories of SPH; hence, only the group of poor SPH was significantly associated with sugary product consumption.…”
Section: Discussionmentioning
confidence: 99%
“…The six top commonly used QoL measurements included the SF-12 which was found in 19 studies [ 35 , 36 , 38 , 39 , 41 , 43 , 45 , 48 , 49 , 51 , 53 , 54 , 60 , 66 , 68 , 70 73 ], the SF-36, identified in 16 studies [ 36 , 42 , 44 , 47 , 50 , 55 , 57 59 , 61 65 , 67 , 69 ], the EuroQoL EQ-5D, included in 8 studies [ 37 , 41 , 44 , 55 , 60 , 71 73 ], the PHQ-9, found in five studies [ 35 , 40 , 60 , 66 , 74 ], the WHOQOL-BREF, evaluated in two studies [ 40 , 52 ], and the ADDQoL19, identified in two studies [ 42 , 46 ].…”
Section: Resultsmentioning
confidence: 99%
“…In terms of mental health measurements, there were four questionnaires that were commonly used which combined with QoL questionnaires namely the WHO-5 in three of the reviewed studies [ 38 , 66 , 74 ], the BDI in three studies [ 47 , 57 , 67 ], the PAID in three studies [ 56 , 66 , 74 ], and lastly the PACIC, found in two studies [ 38 , 49 ].…”
Section: Resultsmentioning
confidence: 99%
“…For example, studies have reported that poorer HRQoL is commonly seen in individuals with diabetes 1 3 and depression 4 . In depressed individuals, greatest reduction in HRQoL is found in those suffering from non-melancholic type of depressive symptoms 5 .…”
Section: Introductionmentioning
confidence: 99%